Caregiver Burden and Its Associated Factors Among Family Caregivers of Hospitalized Patients with Neurocritical Disease: A Cross-Sectional Study - Wei L; Zhao X; Chen X; He Y; Liu J; Xian J; Yang Y (Journal of Multidisciplinary Healthcare)
Li Wei,1,2,* Xingying Zhao,1,2,* Xiaomei Chen,1 Yuxuan He,1 Jia Liu,1 Jishu Xian,2 Yanni Yang1 1School of Nursing, Army Medical University (Third Military Medical University), Chongqing, 434008, People’s Republic of China; 2Neurosurgery Department, the First Affiliated Hospital of Army Medical University (Third Military Medical University), Chongqing, 434008, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yanni Yang, School of Nursing, Army Medical University (Third Military Medical University), No. 30 Gaotanyan Street, Shapingba District, Chongqing, 434008, People’s Republic of China, Email yangyanni@tmmu.edu.cnBackground:  Providing informal care for patients with neurocritical diseases is a challenging job, and family caregivers usually experience psychological distress and high caregiver burden. Previous studies have focused on caregiver burden for patients in the home rehabilitation stage, while few studies investigate caregiver burden among informal caregivers of early postoperative inpatients.Objective: This study aimed to investigate caregiver burden for caregivers of patients with neurocritical diseases during hospitalization and to identify predictive factors related to caregiver burden.Methods: From November 2023 to April 2024, a cross-sectional study was conducted using a convenience sampling method to assess patients with neurocritical disease and their family caregivers. The fundamental data regarding patients and caregivers were examined. Family caregivers were requested to complete the Zarit Burden Interview (ZBI), the Coping Adaptation Processing Scale (CAPS-15), the Chinese Auditory Verbal Learning Test of Huashan Version (AVLT-H), the Multifactorial Memory Questionnaire (MMQ), and the Hospital Anxiety and Depression Scale (HADS-A). The variables associated with caregiver burden were identified through the use of multiple linear regression analyses.Results: 300 patients and their family caregivers participated in the study. Predominantly male family caregivers accounted for 55.7%, and the mean age was 46.7 ± 13.1 years. The patients’ average age was 52.8 ± 14.3 years, 151 (50.3%) were men, and 153 (50.3%) had brain tumors. The average caregiver burden was 33.94 ± 17.2. Family caregivers of inpatients with neurocritical diseases experienced a mild to moderate caregiver burden. Patients’ physical function, caregiver’s age, relationship with patients, comorbid chronic disease status, memory function, adaptation level, and anxiety independently predicted caregiver burden, accounting for 66.3% of the total variation.Conclusion: Family caregivers of inpatients with neurocritical diseases experience mild to moderate level of caregiver burden. Tailored early support plans should be developed based on caregivers’ characteristics, including anxiety strategies, memory support, communication optimization, and role adjustment, to reduce their burden.Keywords: caregiver burden, family caregivers, influencing factors, neurocritical disease, hospitalization